The Intellectual Landscape of Servant Leadership: A Bibliometric Study on Its Relationship with Job Satisfaction - Shibani , Abdussalam; Djoubar , Mohammed; Mahmud , Ahmed (Journal of Science and Knowledge Horizons, 2025)
This study provides a bibliometric analysis of the evolution of servant leadership and its relationship with job satisfaction, focusing on global publication trends, influential contributors, and thematic clusters from 1990 to 2025. Using the Scopus database, 29 relevant studies were analysed to map the field’s intellectual structure. The findings revealed significant growth in publications over the past five years, with notable contributions from the United States, Indonesia, and China. Key journals, including Frontiers in Psychology and Cogent Business and Management, have been pivotal in disseminating research on servant leadership. The analysis highlights themes like the mediating role of trust in the relationship between servant leadership and job satisfaction, the influence of ethical leadership on employee performance, and broader organizational outcomes linked to these styles. Emerging topics include servant leadership in hybrid work environments and cross-cultural contexts, highlighting the field’s dynamic evolution. Despite the growing literature, limitations like the dominance of cross-sectional studies and underrepresentation of non-Western perspectives signal areas for future research. This study offers insights into the intellectual landscape of servant leadership research and its potential to address evolving workplace dynamics, with implications for academic inquiry and organizational practice.